SURVEI PEMBINAAN PRESTASI KLUB-KLUB BULUTANGKIS DI KABUPATEN PEMALANG TAHUN 2014 (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study was to determine the achievement coaching conducted badminton clubs in Pemalang district. Analysis of the data in this research is to reduce the data, presenting data and making inferences. Results of this research is the development of badminton clubs in Pemalang district covers To promote coaching, coaching and coaching achievements nursery. Each club has a training program in the execution of the exercise so that the exercise can be run in accordance exercise program made. Organizational management of the club is still incomplete. Coaches have experience in training and has a coaching license to support the success of the club's coaching. Facilities and infrastructure badminton clubs in Pemalang district is quite good but still lacking for physical development. Funding obtained from the club's monthly dues club athletes, athletes as well as registration of the sponsor club, but not all clubs have a sponsor. The system of coaching athletes badminton clubs in Pemalang district already implementing a system of coaching with reference to the guidance system To promote, nursery coaching, and coaching achievements, but still not good because the nursery athletes not using the scientific method, in addition to the nursery still needs improvement also in the organization and funding,.